DEVELOPMENT OF THE CONCEPT OF MORALITY FROM PHILOSOPHICAL CONTENT INTO CRITIQUE OF SATIRE IN INDIAN ART - Dayal, Deepanjali; Chauhan, Rajesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The development of the concept of satire holds an important place in the philosophical content of Indian art as it has transformed in several ways reflecting the socio-cultural and political changes. Satire has been voiced in Indian art over the years through its varied expressions that are crucial to understanding the hidden content of commentary or the overtly implied motives of satire in different art forms. The purpose of my research is to explore two interdependent concepts, first, the kinship of satire to the concept of Indian moral philosophy; and second, the reflection of moral philosophy through varied expressions of satire in Indian art. Morality has had deep roots in Indian philosophy since ancient times. The moral and ethical framework of philosophy revolves around the concept of ‘Dharma’ that holds immense importance in the philosophical foundation of different schools such as Jainism, Buddhism, and Hinduism. It is also central to the metaphysical identity of the Indian culture that aims to foster ethical conduct through righteousness and justice. Indian art has evolved through the ages as a reflection of society and its influence on the formation of culture and values. Teachings of morality have been integral to the Indian culture rather than the biting language of satire that found its expressions in Indian art around the later stages of development, that is around the medieval period when a deeper inflow of foreign influence began entering the Indian cultural system. I aim to understand the evolution of morality from the ancient period progressing toward the critical harsh mockery of satire in contemporary Indian art.